Humans' relationship to nature – framing sustainable marketing. Issue 1 (13th February 2017) - Löbler, Helge
Abstract : Purpose: Although humans are part of nature, the relationship between humans and nature is not well understood, neither in sustainable marketing nor in relationship marketing. Nature is damaged by humans, and a lot of natural resources coming from nature are taken for granted. The services provided by nature are also often taken for granted. However, humans cannot live without these services, but nature can probably survive without humans, especially man-made (artificial) services. The paper aims to offer a frame that allows aligning marketers and academics' understanding of service with that of sustainability for sustainable marketing. Design/methodology/approach: A literature review of different literature streams, biological, ecological and service literature shows that service is a much broader phenomenon as discussed in the service literature. The paper will show that a fundamental relationship between either humans or humans and nature is service as defined here. Service is understood here as an ongoing process of exchange and change. Service as proposed here is a form of coexistence. Findings: Service will be defined as an ongoing process of exchange and change (transfer and transformation) of resources. This understanding integrates human and natural service without connecting it only to human intentions, wishes or needs as causation for service. The process of service as conceptualized here is in line with the understanding of sustainability, as it is discussed nowadays. Aligning marketers' understanding of service with that of sustainability gives a new frame for sustainable marketing. Research limitations/implications: The work may be understood as a step toward a sustainable marketing by framing sustainable processes from a service perspective. The holistic understanding of sustainable marketing offers new chances not only for further research but also for a better (more sustainable) understanding of day-to-day practices. Practical implications: If humans understand the fundamental relationship with nature, it can help to act in harmony with nature and not against it to improve sustainable development based on a better understanding of human's relationship with nature. Social implications: Mainstream sustainable marketing is sometimes based on a strong anthropocentrism. This paper balances the role of humans toward nature. Originality/value: It is the first paper in relationship marketing looking at the relationship with nature and uses this view to frame this concept of sustainable marketing.